Sulfur Derivatives of 1,2,4-Triazole: Recently Developed Compounds, Structure Activity Relationship, and Biological Activity: Review article - Jasim, Azhar Mahdi; Omar, Tagreed N-A; Abdulhadi, Shayma L. (Iraqi Journal of Pharmaceutical Sciences, 2024)
The term of heterocyclic chemistry focuses only on heterocyclic compounds, which consider as a percentage of organic chemistry, they equal to greater than sixty-five. These compounds are widely founded in nature and most of them are important to life. In the past few years, scientist fused on 1,2,4-triazoles and their condensed heterocyclic ring due to their medicinal significance, 1,2,4-triazole containing Sulphur atom is one of the important heterocyclic moieties due to its broad range of biological activities also their derivatives can accommodate one of the alternatives as electronic effect as exchanges of the electronic density (electron donating or withdrawing) groups ; for all what mentioned above they are consider as a core molecule in development of large number of medicinal compounds. 1,2,4-Triazole have wide range of pharmacological motivating drug possibility such as analgesic, anti-microbial, anti-inflammatory, anti-convulsant, antioxidant, anti-septic, anti-cancer, diuretics, anti-diabetic, anti-urease, and anti-migraine agents. This review focus on 1,2,4-triazole Sulfur based compounds about their different biological activities and the relationship with their chemistry.